Needs Analysis of Edupreneurship Learning in the English Language Education Study Program - Shilfani Shilfani; Mey Enggane Limbongan (Universitas Cokroaminoto Palopo, 2022)
Edupreneurship is a science that seeks to integrate entrepreneurship ideas, concepts, and attitudes into the world of education. Needs analysis is the first step in determining the problem overview, correcting, and finding problem solving to design the program from the next course. The goal of this research is to determine the needs of students in the Edupreneurship Course of the English Study Program, FKIP, UKI Toraja. The development method (Research and development/ R&D) was used in this study. Borg and Gall (1979:772) state that